PD-L1 Improves Motor Function and Alleviates Neuropathic Pain in Male Mice After Spinal Cord Injury by Inhibiting MAPK Pathway - Kong, Fanqi; Sun, Kaiqiang; Zhu, Jian; Li, Fudong; Lin, Feng; Sun, Xiaofei; Luo, Xi; Ren, Changzhen; Lu, Lantao; Zhao, ShuJie; Sun, Jingchuan; Wang, Yuan; et al. (Frontiers in Immunology, 2021)
Background Traumatic spinal cord injury (SCI) causes severe motor dysfunction and persistent central neuropathic pain (Nep), which has not yet been effectively cured. Programmed cell death ligand-1 (PD-L1) is typically produced by cancer cells and contributes to the immune-suppressive in tumor microenvironment. However, the role of PD-L1 in regulating inflammatory response and Nep after SCI remains unclear. A growing amount of researches have begun to investigate the effect of PD-L1 on macrophages and microglia in recent years. Considering the pivotal role of macrophages/microglia in the inflammatory response after SCI, we proposed the hypothesis that PD-L1 improved the recovery of locomotor and sensory functions after SCI through regulating macrophages and microglia. Methods The mice SCI model was established to determine the changes in expression patterns of PD-L1. Meanwhile, we constructed PD-L1 knockout mice to observe differences in functional recovery and phenotypes of macrophages/microglia post-SCI. Results In present study, PD-L1 was significantly upregulated after SCI and highly expressed on macrophages/microglia at the injury epicenter. PD-L1 knockout (KO) mice showed worse locomotor recovery and more serious pathological pain compared with wild-type (WT) mice. Furthermore, deletion of PD-L1 significantly increased the polarization of M1-like macrophages/microglia. Mechanistic analysis revealed that PD-L1 may improve functional outcomes following SCI by inhibiting phosphorylation of p38 and ERK1/2. Conclusions Our observations implicate the involvement of PD-L1 in recovery of SCI and provide a new treatment strategy for the prevention and treatment of this traumatic condition.